DAMPAK PROGRAM FUNDRAISING LEMBAGA AMIL ZAKAT DAN SHADAQAH MUHAMMADIYAH (LAZISMU) KABUPATEN MAGELANG YAITU FILANTROPIS CILIK TERHADAP MIM PAREMONO - Aprilia Rizka Rahmawati; Haifa Nurilfaruqi (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
The Zakat, Infaq and Shadaqah Amil Institution (LAZISMU) is an institution established by the Muhammadiyah community organization that plays a role in collecting, managing, and distributing zakat, infaq, and shadaqah funds (ZIS). LAZISMU has a fundraising/collection program, including young philanthropists. This study aims to determine the impact of the young philanthropist program on educational institutions. This study uses a qualitative approach to obtain information. The sources of this research are primary and secondary data obtained from interviews, observations, and documentation. The results of this study formulate conclusions regarding the impact of the young philanthropist program, especially at MIM Paremono.